The measurement of the alveolar bone crest in aggressive periodontitis using Cone Beam Computed Tomography imaging - Lestari, Astia Dwiputri; Azhari, Azhari; Wendari, Sri (Universitas Padjadjaran, 2012)
The normal alveolar bone crest located at a distance of 1 to 2 mm from CEJ towards the apical. If there is a bone loss, the alveolar bone crest located at 2 mm more to the apical from CEJ. The alveolar bone loss is one characteristic of aggressive periodontitis and the onset of the disease at the age of puberty. The purpose of this research was to know and to assess the height of alveolar bone crest using Cone Beam Computed Tomography (CBCT) in patients with aggressive periodontitis. The type of this research was descriptive. A total of 317 sample CBCT imagery from 6 aggressive periodontitis patients. The result of this research showed that average height of alveolar bone crest second premolar distal, the first molar mesial, first molar distal and second molar mesial on the first region were 3 mm, 4.2 mm, 6.1 mm, and 4.8 mm respectively. On the second region were 3.2 mm, 3.6 mm, 3.6 mm, and 3.4 mm respectively, and in the third region were 2.4 mm, 2.8 mm, 2.5 mm dan 1.4 mm consecutively. While in the fourth region were 2.9 mm, 3 mm, 2.8 mm, and 2.3 mm respectively. The average height of alveolar bone crest of aggressive periodontitis was 3.8 mm. Slicing CBCT imagery on coronal view for the anterior region and sagittal view for the posterior region, showed the characteristic of height alveolar bone crest was arch-shaped which showed the different height of alveolar bone crest of the second premolar distal until second molar mesial.